Trade Openness and Spatial Distribution of Manufacturing Industries: Iranian Provincial Evidence - Ardeshiri, Mansour; Moghaddasi, Reza; Yazdani, Saeed; Mohamadinejad, Amir (Asian Journal of Applied Economics, 2019)
This paper aims to study the impact of trade openness on the spatial concentration of economic activities of manufacturing industries within the framework of New Economic Geography (NEG) theory. A three-step approach was used for testing the research hypothesis. The stationary test results of variables, in the first step, indicated that the variables are I (1). The results of the Pedroni panel cointegration test specified a long-run relationship between variables. In the third step, using GMM and fixed effects methods, the specified model was estimated for 28 provinces of Iran from 2004 - 2013. The findings show that trade openness has a negative and significant effect on the geographical distribution of manufacturing industries in the provinces of Iran. Indeed, the export promotion policies since the 1990s have led to the dispersion of manufacturing industries in the Iran provinces.